Dynamics in the vicinity of (101955) Bennu: Solar radiation pressure effects in equatorial orbits - Chanut, T. G.G. [UNESP]; Aljbaae, S. [UNESP]; Prado, A. F.B.A.; Carruba, V. [UNESP] (Oxford University Press (OUP), 2017)
Here, we study the dynamical effects of the solar radiation pressure (SRP) on a spacecraftthat will survey the near-Earth rotating asteroid (101955) Bennu when the projected shadowis accounted for. The spacecraft's motion near (101955) Bennu is modelled in the rotatingframe fixed at the centre of the asteroid, neglecting the Sun gravity effects. We calculate theSRP at the perihelion, semimajor axis and aphelion distances of the asteroid from the Sun.The goals of this work are to analyse the stability for both homogeneous and inhomogeneousmass distribution and study the effects of the SRP in equatorial orbits close to the asteroid(101955) Bennu. As results, we find that the mascon model divided into 10 equal layers seemsto be the most suitable for this problem. We can highlight that the centre point E8, which waslinearly stable in the case of the homogeneous mass distribution, becomes unstable in this newmodel changing its topological structure. For a Sun initial longitude ψ0 = -180°, startingwith the spacecraft longitude λ = 0, the orbits suffer fewer impacts and some (between 0.4and 0.5 km), remaining unwavering even if the maximum solar radiation is considered. Whenwe change the initial longitude of the Sun to ψ0 = -135°, the orbits with initial longitudeλ = 90° appear to be more stable. Finally, when the passage of the spacecraft in the shadowis accounted for, the effects of SRP are softened, and we find more stable orbits.
Keywords: Celestialmechanics; Gravitation; Methods: numerical; Minor planets, asteroids: individual: (101955) Bennu